Poles in resistance under German uniform: A singular experience of underground warfare in occupied Belgium, 1914–1918 - Debruyne, Emmanuel (Polonia Inter Gentes, 2025)
During World War I, hundreds of thousands of Poles served in the German army, with some participating in the occupation of Belgium. This article focuses on the unique experience of a small group of them, often from the province of Posen, who became involved in the Belgian resistance against Germany. Several of them used their position within the occupying forces to pass on information to Belgian intelligence networks, such as Golenvaux and Wasseige. The best-documented case is that of Marian Szeszycki, a guard in the German section of the Liège prison. Szeszycki took advantage of his position to assist Allied agents imprisoned there and became involved in an actual resistance network operating within the prison itself, which worked closely with the Dame Blanche, the largest Allied intelligence network in occupied territory. In 1918, Szeszycki successfully helped two deathrow prisoners escape and, in the process, deserted himself. As a former German soldier, Szeszycki could have been expelled from Belgium after the war, but he gained the support of former resistance members he had worked with, allowing him to settle in Belgium for a time. His actions, as well as those of his counterparts involved in other networks, did not go entirely unnoticed. Even though the authorities were reluctant to grant them official recognition, their activities were made public, especially within Belgian Catholic circles. In the years leading up to World War II, as rising international tensions raised fears of a new invasion of Belgium and Poland, Szeszycki’s name even appeared in several books about the secret war of 1914–1918, contributing to a favorable image of Poland among Western countries.